READINESS OF SCHOOL LEADERS IN MALAYSIA TO FACE THE VUCA (VOLATILE, UNCERTAIN, COMPLEX, AMBIGUOUS) ERA: A RECENT COMPREHENSIVE STRUCTURED REVIEW - Graciella, Mutil; Abdul Halim, Busari; Mohammad Nur Azhar, Mazlan; Andrew Thomas, Ujil (GLOBAL ACADEMIC EXCELLENCE (M) SDN BHD, 2024)
The current era, characterized by volatility, uncertainty, complexity, and ambiguity (VUCA), presents significant challenges for school leaders globally, including in Malaysia. This systematic literature review aims to assess the readiness of Malaysian school leaders to navigate these challenges effectively. The study addresses the pressing issue of whether current leadership practices and training are sufficient to equip leaders with the necessary skills and competencies. To achieve this, we conducted an extensive search of scholarly articles from reputable databases such as Scopus and Web of Science, focusing on studies published between 2020 and 2024. The flow of study based on PRISMA framework. The database found (n=18) final primary data was analysed. The finding was divided into three themes which is (1) Leadership in Turbulent and Uncertain Times, (2) Inclusivity and Equity in School Leadership and (3) Technological Integration and Innovation in Education. The findings underscore the urgency for policy reforms and the implementation of comprehensive training frameworks to bolster leadership capabilities in the education sector. In conclusion, while there are pockets of excellence, the overall readiness of Malaysian school leaders to face the VUCA era is insufficient, necessitating immediate and sustained efforts to enhance their preparedness through strategic initiatives and continuous professional development.